28x^2 - 47x = 15
28x^2 - 47x - 15 = 0
ax^2 + bx +c = 0,
so:
a = 28
b = -47
c = -15
[-b^2 + sqrt(4*a*c)] / 2*a AND
[-b^2 - sqrt(4*a*c)] / 2*a
[47^2 + sqrt(4*28*-15)] / 2*28 AND
[47^2 - sqrt(4*28*-15)] / 2*28
then just do the math
Solve using the quadratic formula
Using the quadratic equation formula:- x = 3.795831523 or x = -5.795831523
-2x2 + 9x - 12 = 0Then apply the quadratic formula.
If you can't factor it easily, use the quadratic formula.
The Quadratic formula in mathematics is used to solve quadratic equations in algebra. The simplest way to solve these equations is to set each of the factors to zero and then solve each factor separately.
Solve using the quadratic formula
Quadratic equation formula
Using the quadratic equation formula:- x = 3.795831523 or x = -5.795831523
-2x2 + 9x - 12 = 0Then apply the quadratic formula.
The quadratic formula is used to solve the quadratic equation. Many equations in which the variable is squared can be written as a quadratic equation, and then solved with the quadratic formula.
If you can't factor it easily, use the quadratic formula.
If you can't factor it easily, use the quadratic formula.
The Quadratic formula in mathematics is used to solve quadratic equations in algebra. The simplest way to solve these equations is to set each of the factors to zero and then solve each factor separately.
I suggest you use the quadratic formula. In this case, a = 1, b = 5, c = 3.
It can be solved by using the quadratic equation formula.
X= (3/5 , -2)
a2+30a+56=0 , solve for a Using the quadratic formula, you will find that: a=-2 , a=-28